PRILAKU KEJAHATAN MEMPERDAGANGKAN MANUSIA /TPPO (HUMANS TRAFFICKING)DALAM PRESPEKTIF HUKUM PIDANA POSITIF INDONESIA - Dimas Arif Pratama; Basyarudin Basyarudin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Human Trafficking Crime Behaviour / TPPO from the perspective of criminal law in Indonesia is a very complex crime and difficult to eradicate. Human Trafficking Crime Behaviour has a tendency to occur by involving the complexity of life that covers several fields of life. Human trafficking crimes often occur within or outside the country. However, the discussion on human trafficking focuses more on women as a vulnerable group. All of this can be proven in several incidents from time to time without knowing the era. Therefore, the author conducts this research to find out what criminal sanctions should be given to the perpetrators of criminal acts of trafficking in persons based on positive criminal law. The research model chosen is a literacy research model using data from primary sources (primary) and additional sources (secondary). The main reference is the Law on the Crime of Trafficking in Persons Number 21 of 2007, but the supporting data comes from relevant fiqh books and law books. The data analysis tool uses a more positive descriptive analysis by adopting and considering the concept of positive crime by explaining the data obtained in the context of human trafficking crimes (TPPO) according to Indonesian positive criminal law, with the hope that data accuracy can be obtained. Laws that bring about legal reform. The results obtained in the research provide an illustration that according to the Law on the Crime of Trafficking in Persons Number 21 of 2007, perpetrators who are proven to have violated will be sentenced to prison between 3 to a maximum of life, as well as fines ranging from 120 million to 800 million rupiah, and penalties higher. This shows that it has been implemented. For business. Sanctions vary depending on the type and classification of sanctions application